NEGATIVE PREFIX IN THE DIGITAL NEWS OF RUSSIA – UKRAINE WAR BY CNN - Fristi Arfiawati; Hesti Lestari (Jurnal Sastra - Studi Ilmiah Sastra, 2023)
The research entitled Negative Prefix in the Digital News of Russia-Ukraina War by CNN used the theory from Yule (2010) and it was supported by the theory from Handoko et.al (2019) and Sitorus et.al (1993). The aim of this research is to investigate the negative prefix in the digital news of Russia-Ukraina war.  In addition, this research applied descriptive qualitative method, moreover the data which were obtained from digital news of CNN about Russia_Ukraina War were classified and analyzed. The data found were 22 data of negative prefix and the result showed that the data comprised into 11 negative prefix un-,  9 negative prefix in- (im-, ir-, il-), 1 negative prefix mis-, and 1 negative prefix dis-. Furthermore, there are 69%  negative prefix attached to adjective,  9%  negative prefix attached to noun, 13%  negative prefix attached to verb, and 9% negative prefix attached to adverb.  Thus, the most dominant of negative prefix used in the CNN digital news is negative prefix un-. In addition, the negative prefix attached to adjective is mostly used in the article of Rusia-Ukraina CNN digital news.